Nursing perspective of the expert consensus on diagnosis and treatment of integrated Chinese and Western medicine in lung cancer - Jing Zhang; Tao Ma; Shuhong Liu; Yan Zhao; Ling Tang (Journal of Integrative Nursing, 2022)
Lung cancer is a malignant tumor with the highest incidence and mortality in China, which seriously affects the quality of life of patients. Traditional Chinese medicine (TCM) plays a unique advantage in the treatment and rehabilitation of lung cancer. In order to standardize TCM diagnosis and treatment and disease management of clinical medical workers, the Chinese Association of Integrative Medicine issued the “Expert Consensus on the Diagnosis and Treatment of Lung Cancer by Integrated Traditional Chinese and Western Medicine” in August 2021. Experts' recommendations were made on the clinical staging and syndrome differentiation and classification of lung cancer, characteristic TCM therapies, and nursing care of integrated traditional Chinese and Western medicine. This article interpreted the Consensus on the above aspects from a nursing perspective, hoping to provide references for clinical medical workers in the treatment and nursing care of lung cancer.